2014
DOI: 10.1080/15248372.2013.784975
|View full text |Cite
|
Sign up to set email alerts
|

Core Knowledge and the Emergence of Symbols: The Case of Maps

Abstract: Map reading is unique to humans but present in people of diverse cultures, at ages as young as 4 years. Here we explore the nature and sources of this ability, asking both what geometric information young children use in maps and what non-symbolic systems are associated with their map-reading performance. Four-year-old children were given two tests of map-based navigation (placing an object within a small 3D surface layout at a position indicated on a 2D map), one focused on distance relations and the other on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 57 publications
(84 reference statements)
3
17
0
Order By: Relevance
“…These results are inconsistent with the hypothesis that pictures facilitate representations of scenes and objects that rely equally on extended surface and landmark shape information. Instead, they are consistent with past findings that young children rely selectively on different geometric information when using overhead maps to find targets located either at the midpoint of extended surfaces in the environment or at landmarks in that environment (Huang & Spelke, ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results are inconsistent with the hypothesis that pictures facilitate representations of scenes and objects that rely equally on extended surface and landmark shape information. Instead, they are consistent with past findings that young children rely selectively on different geometric information when using overhead maps to find targets located either at the midpoint of extended surfaces in the environment or at landmarks in that environment (Huang & Spelke, ).…”
Section: Resultssupporting
confidence: 90%
“…Both Huang and Spelke () and Dillon et al . () adopted an individual differences approach to probe the relationships between children's sensitivity to distance and angle when they navigate, recognize objects, and interpret spatial symbols.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, disoriented children also fail to encode angle relationships between surfaces, and they encode distance relationships between wall-like surfaces but not between freestanding objects or fragmented corners (Gouteux and Spelke, 2001;Lee and Spelke, 2008;Lee and Spelke, 2010;Lee and Spelke, 2011;Lee et al, 2012a). Importantly, children use these geometric properties not only to solve the navigation problems faced by other animals, but also to solve the uniquely human problem of navigating by a map (Huang and Spelke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Huang and Spelke (25) showed that children's use of distance in a nonsymbolic navigation task correlated with their use of a map to locate targets at the surface midpoints of a continuous triangular environment. Moreover, children's use of angle and relative length in a nonsymbolic shape recognition task correlated with their use of a map to locate targets at the corners of the same triangular environment.…”
mentioning
confidence: 99%